Vulcanized rubber with vulcanization network structure regulated and controlled by sulfur-containing regulator and preparation method of vulcanized rubber

By introducing sulfur-containing regulators into polyisoprene rubber to regulate the vulcanization network structure and adding polysulfide bonds, the problem of insufficient performance is solved, and high-performance, self-healing and recyclable vulcanized rubber is achieved, suitable for extended applications and Environmental protection needs.

CN119192621AActive Publication Date: 2024-12-27SICHUAN UNIV

Patent Information

Application Number
CN202411463699.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-27
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

Polyisoprene rubber has poor tensile properties, tear resistance and fatigue resistance, which limits its application range. Moreover, sulfur vulcanization technology has difficulties in waste rubber treatment and microcrack repair, affecting environmental protection and sustainable development. .

Method used

By introducing sulfur-containing regulators to regulate the vulcanization network structure, high-performance modified vulcanized rubber is prepared, the content of polysulfide bonds is increased to improve mechanical properties, and complete polysulfide bonds are introduced into the vulcanization network to achieve self-healing and recyclable characteristics.

Benefits of technology

Achieve excellent mechanical properties, excellent self-healing properties (self-healing efficiency is 89.8%) and high recyclability (recovery rate is 104%) of polyisoprene rubber, which significantly improves the performance of vulcanized rubber and is suitable for industrial use. It has cost advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192621A_ABST
    Figure CN119192621A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of rubber, and particularly relates to vulcanized rubber with a vulcanization network structure regulated and controlled by a sulfur-containing regulator and a preparation method of the vulcanized rubber. Specifically, the invention provides a method for preparing vulcanized rubber with a vulcanized network structure regulated and controlled by a sulfur-containing regulator, and the method comprises the step of vulcanizing 100 parts by weight of raw rubber in the presence of 0.5-2 parts by weight of the sulfur-containing regulator, so as to obtain the vulcanized rubber with high mechanical property and creep resistance. The invention further provides a method for preparing the vulcanized rubber with the sulfur-containing regulator for regulating and controlling the vulcanization network structure, and the method comprises the step of vulcanizing 100 parts by weight of raw rubber in the presence of 3-8 parts by weight of the sulfur-containing regulator, so that the vulcanized rubber with high mechanical properties and recovery and self-healing properties is obtained. The performance of the vulcanized rubber is remarkably improved through the method which is simple and easy to operate, and the method is very suitable for industrial application and popularization and has the excellent cost advantage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber, and in particular relates to a vulcanized rubber with a vulcanization network structure regulated by a sulfur-containing regulator and a preparation method thereof. Background Art

[0002] Natural rubber (NR) material is an important industrial raw material, widely used in the manufacture of tires, rubber products and aerospace. Although synthetic polyisoprene rubber (PIP) has a similar main chain structure and molecular weight to natural rubber, the performance of polyisoprene rubber is poor, especially the tensile properties, tear resistance and fatigue resistance, which are far behind the performance of natural rubber, which seriously limits its practical use value. Sulfur vulcanization, as an important rubber processing technology, can improve the comprehensive performance of products, improve product quality and durability. However, they also bring great difficulties to the repair of internal microcracks and the recycling of waste rubber. The treatment of waste rubber has become a global environmental, social and economic issue. Therefore, from the perspective of green chemistry and sustainable development, it is very important to develop high-performance, recyclable and self-healing rubber materials. Therefore, this patent regulates the structure of the rubber vulcanization network by introducing a sulfur-containing regulator, thereby preparing high-performance, recyclable and self-healing polyisoprene rubber. This is of great significance for expanding the application field of polyisoprene rubber and green sustainable development. Summary of the invention

[0003] The present invention proposes a simple method for preparing high-performance modified vulcanized rubber by adjusting the composition and content of cross-linked bonds in the vulcanization network. On the one hand, the higher content of polysulfide bonds in the modified vulcanized rubber gives it excellent SIC ability, thereby obtaining excellent mechanical properties. On the other hand, we also prepared vulcanized rubber with self-healing and recyclable properties by introducing complete polysulfide bonds in the vulcanization network. The polysulfide bonds in the rubber sample can undergo rapid exchange reactions under temperature stimulation. This unique property not only gives the cross-linked rubber excellent self-healing properties (self-healing efficiency of 89.8%), but also brings excellent recyclability (recycling rate of 104%).

[0004] Specifically, in the first aspect, the present invention provides a method for preparing a vulcanized rubber having a vulcanization network structure regulated by a sulfur-containing regulator, which comprises vulcanizing 100 parts by weight of raw rubber in the presence of 0.5-2 parts by weight of a sulfur-containing regulator to obtain a vulcanized rubber having high mechanical properties and creep resistance.

[0005] Further, the raw rubber is at least one of EPDM rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, polybutadiene rubber, butyl rubber, nitrile rubber, styrene / butadiene block copolymer, polyisoprene rubber, polynorbornene, unsaturated polyester rubber, epoxidized butadiene rubber, epoxidized isoprene rubber, epoxidized styrene / butadiene block copolymer and epoxidized styrene / isoprene block copolymer. Preferably, the raw rubber is polyisoprene rubber.

[0006] Furthermore, the sulfur-containing regulator is a dithiol compound.

[0007] Furthermore, the sulfur-containing regulator is selected from at least one of the following compounds:

[0008]

[0009] Further, the sulfur-containing regulator is, for example, at least one of benzenedithiol (BED), lipoic acid (LA), 4',4-dithioldiphenyl sulfide (TBBT), dithiothreitol (DTT), 4,4-diaminodiphenyl disulfide (APDS), 2,5-diamino-1,4-benzenedithiol dihydrochloride (DPDD), bis(4-aminophenyl) sulfide (TDA), p-toluene disulfide (PTD), 4-aminothiophenol, 3-aminothiophenol, 2-aminothiophenol, 4-(phenylthio)aniline, butanedithiol and hexanedithiol.

[0010] Preferably, the weight portion of the sulfur-containing regulator is 0.5-1 part.

[0011] Furthermore, the method further comprises adding 30-50 parts by weight of carbon black or white carbon black.

[0012] Furthermore, the vulcanization includes adding a vulcanizing agent by means of double-roll milling or solution blending, and then vulcanizing and molding at a high temperature.

[0013] Furthermore, the vulcanizing agent is sulfur, tetramethylthiuram disulfide (TMTD), dipentamethylenethiuram tetrasulfide (DPTT) (TRA), 4-(2-benzothiazolyl disulfide)morpholine (MDB), tetraethylthiuram disulfide (TETD), tetrabutylthiuram disulfide (TBTD), tetramethylthiuram tetrasulfide (TMTT), 4,4'-dimorpholine disulfide (DTDM), N,N-polysulfide bis(dimethylamine), N,N'-polysulfide bis(diethylamine), cyclohexylthiuram disulfide (CTS ... Preferably, the vulcanizing agent is at least one of diisocyanate, dicumyl peroxide (DCP), di-tert-butyl peroxide (DTBP), 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DBPMH), benzoyl peroxide (BPO), 2,4-dichlorobenzoyl peroxide (DCPB), tert-butyl perbenzoate (TBPB), di-tert-butyl peroxyisocyanate (BIPB), 3,3,5,7,7-pentamethyl-1,2,4-triepoxyhexane (PMTO), and cumyl hydroperoxide (CHP). Preferably, the vulcanizing agent is sulfur.

[0014] Furthermore, the vulcanization further comprises adding auxiliary agents, and the auxiliary agents include zinc oxide, stearic acid, antioxidants, anti-aging agents and / or vulcanization accelerators.

[0015] Further, the antioxidant may be N-1,3-dimethylbutyl-N′-phenyl-p-phenylenediamine.

[0016] Furthermore, the antioxidant may be poly(1,2-dihydro-2,2,4-trimethylquinoline).

[0017] Furthermore, the vulcanization accelerator may be N-cyclohexyl-2-benzothiazolesulfonamide.

[0018] Furthermore, the weight proportion of the added vulcanizing agent is 1-3 parts, preferably 2 parts.

[0019] Furthermore, the weight proportions of zinc oxide, stearic acid, antioxidant, anti-aging agent and vulcanization accelerator added are 3-8 parts, 1-4 parts, 1-3 parts, 1-3 parts and 0.5-3 parts respectively.

[0020] As described herein, the specific process of vulcanizing the raw rubber using the vulcanizing agent and the auxiliary agent of the present invention is well known to those skilled in the art and can be adjusted routinely, for example, the exemplary vulcanization process described in the embodiments of this specification or any other suitable process can be used. For example, the vulcanization conditions can be: the hot pressing temperature is 120-190°C, for example, 150-160°C; the pressure is 7-20MPa, for example, 8-12MPa; the time is 15-120min, for example, 20-40min.

[0021] The present invention also provides a vulcanized rubber having high mechanical properties and creep resistance, which is prepared by the method described above.

[0022] In a second aspect, the present invention provides a method for vulcanizing rubber with a sulfur-containing regulator to regulate the vulcanization network structure, which comprises vulcanizing 100 parts by weight of raw rubber in the presence of 3-8 parts by weight of the sulfur-containing regulator to obtain a vulcanized rubber with high mechanical properties and recovery and self-healing properties.

[0023] Further, the raw rubber is at least one of EPDM rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, polybutadiene rubber, butyl rubber, nitrile rubber, styrene / butadiene block copolymer, polyisoprene rubber, polynorbornene, unsaturated polyester rubber, epoxidized butadiene rubber, epoxidized isoprene rubber, epoxidized styrene / butadiene block copolymer and epoxidized styrene / isoprene block copolymer. Preferably, the raw rubber is polyisoprene rubber.

[0024] Furthermore, the sulfur-containing regulator is a dithiol compound.

[0025] Furthermore, the sulfur-containing regulator is selected from at least one of the following compounds:

[0026]

[0027] Further, the sulfur-containing regulator is, for example, at least one of benzenedithiol (BED), lipoic acid (LA), 4',4-dithioldiphenyl sulfide (TBBT), dithiothreitol (DTT), 4,4-diaminodiphenyl disulfide (APDS), 2,5-diamino-1,4-benzenedithiol dihydrochloride (DPDD), bis(4-aminophenyl) sulfide (TDA), p-toluene disulfide (PTD), 4-aminothiophenol, 3-aminothiophenol, 2-aminothiophenol, 4-(phenylthio)aniline, butanedithiol and hexanedithiol.

[0028] Furthermore, the method further comprises adding 30-50 parts by weight of carbon black or white carbon black.

[0029] Furthermore, the vulcanization includes adding a vulcanizing agent by means of double-roll milling or solution blending, and then vulcanizing and molding at a high temperature.

[0030] Furthermore, the vulcanizing agent is sulfur, tetramethylthiuram disulfide (TMTD), dipentamethylenethiuram tetrasulfide (DPTT) (TRA), 4-(2-benzothiazolyl disulfide)morpholine (MDB), tetraethylthiuram disulfide (TETD), tetrabutylthiuram disulfide (TBTD), tetramethylthiuram tetrasulfide (TMTT), 4,4'-dimorpholine disulfide (DTDM), N,N-polysulfide bis(dimethylamine), N,N'-polysulfide bis(diethylamine), cyclohexylthiuram disulfide (CTS ... Preferably, the vulcanizing agent is at least one of diisocyanate, dicumyl peroxide (DCP), di-tert-butyl peroxide (DTBP), 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DBPMH), benzoyl peroxide (BPO), 2,4-dichlorobenzoyl peroxide (DCPB), tert-butyl perbenzoate (TBPB), di-tert-butyl peroxyisocyanate (BIPB), 3,3,5,7,7-pentamethyl-1,2,4-triepoxyhexane (PMTO), and cumyl hydroperoxide (CHP). Preferably, the vulcanizing agent is sulfur.

[0031] Furthermore, the vulcanization further comprises adding auxiliary agents, and the auxiliary agents include zinc oxide, stearic acid, antioxidants, anti-aging agents and / or vulcanization accelerators.

[0032] Further, the antioxidant may be N-1,3-dimethylbutyl-N′-phenyl-p-phenylenediamine.

[0033] Furthermore, the antioxidant may be poly(1,2-dihydro-2,2,4-trimethylquinoline).

[0034] Furthermore, the vulcanization accelerator may be N-cyclohexyl-2-benzothiazolesulfonamide.

[0035] Furthermore, the weight proportion of the added vulcanizing agent is 1-3 parts, preferably 2 parts.

[0036] Furthermore, the weight proportions of zinc oxide, stearic acid, antioxidant, anti-aging agent and vulcanization accelerator added are 3-8 parts, 1-4 parts, 1-3 parts, 1-3 parts and 0.5-3 parts respectively.

[0037] Preferably, the added vulcanization accelerator is in an amount of 1 part by weight.

[0038] As described herein, the specific process of vulcanizing the raw rubber using the vulcanizing agent and the auxiliary agent of the present invention is well known to those skilled in the art and can be adjusted routinely, for example, the exemplary vulcanization process described in the embodiments of this specification or any other suitable process can be used. For example, the vulcanization conditions can be: the hot pressing temperature is 120-190°C, for example, 150-160°C; the pressure is 7-20MPa, for example, 8-12MPa; the time is 15-120min, for example, 20-40min.

[0039] The present invention also provides a self-healing and recyclable vulcanized rubber prepared by the method described above.

[0040] Beneficial Effects of the Invention

[0041] The present invention has found that in the process of vulcanization of raw rubber (such as polyisoprene rubber), the composition and content of cross-linked bonds in the vulcanization network can be adjusted by simply adding a specific proportion of sulfur-containing regulators, thereby preparing high-performance modified vulcanized rubber. On the one hand, the higher content of polysulfide bonds in the modified vulcanized rubber gives it excellent SIC ability, thereby obtaining excellent mechanical properties. On the other hand, by introducing complete polysulfide bonds in the vulcanization network, vulcanized rubber with self-healing and recyclable properties can also be prepared. The polysulfide bonds in the rubber sample can undergo rapid exchange reactions under temperature stimulation. This unique property not only gives the cross-linked rubber excellent self-healing properties (self-healing efficiency of 89.8%), but also brings excellent recyclability (recovery rate of 104%).

[0042] The invention realizes significant improvement of the performance of vulcanized rubber through a simple and easy-to-operate method, is very suitable for industrial application and promotion, and has excellent cost advantage. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The vulcanization curves of (a) BED-x and (b) BTD-x samples at 143 °C are shown. (c) T90 values ​​and ΔS values ​​of BED-x and BTD-x samples. (e) Crosslinking density, swelling ratio, and gel fraction of BED-x and (f) BTD-x samples.

[0044] Figure 2 The DSC curves of (a) BED-x sample and (b) BTD-x sample are shown.

[0045] Figure 3 Fourier transform infrared spectra of (a) BED-x and (b) BTD-x samples are shown. The contents of disulfide bonds and polysulfide bonds in (c) BED-x and (d) BTD-x samples are shown.

[0046] Figure 4 Stress-strain curves of (a) BED-x and (b) BTD-x samples are shown. (c) Stress-strain curves of representative samples with the best mechanical properties. (d) Tensile strength, toughness, and tear strength of representative samples. (e) Mooney-Rivlin curves of representative samples. (f) Fitting values ​​of Gc and Ge.

[0047] Figure 5The WAXD patterns of (a) PIP and (b) BED-1 samples at different strains are shown. (c) Magnified image of the WAXD pattern. (d) Fitting curve of PIP at maximum strain. (e) The relationship between the crystallinity index and strain for PIP, BED-0.5, BED-1, and BTD-0.125 samples.

[0048] Figure 6 Storage modulus and tan δ curves of (a) PIP, BED-0.5, BED-1, and BTD-0.125 samples are shown. Creep and recovery curves of PIP, BED-0.5, BED-1, and BTD-0.125 samples at (b) 30°C, (c) 60°C, (d) 90°C, (e) 120°C, and (f) 150°C.

[0049] Figure 7 (a) The vulcanization curve of BED-xy sample at 143°C is shown. (b) T90 and ΔS values ​​of BED-xy sample. (c) Crosslink density, swelling ratio and gel fraction of BED-x-1 and (d) BED-x-1.5 samples.

[0050] Figure 8 Shown are a) Fourier transform infrared spectra of BED-xy samples. (b) The contents of monosulfide bonds, disulfide bonds, and polysulfide bonds in BED-xy samples. (c) Fourier transform infrared spectra of BED-4-1 and corresponding recovered samples. (d) Fourier transform infrared spectra of BED-5-1 and corresponding recovered samples.

[0051] Fig. 9 (a) Stress-strain curve of BED-xy sample. (b) Tensile strength, toughness and fracture strain of BED-xy sample. Creep and recovery curves of BED-xy sample at (c) 30℃ and (d) 90℃.

[0052] Fig.10 Stress relaxation curves of (a) BED-4-1, (b) BED-5-1 and (c) BED-3-1.5 samples at different temperatures are shown. (d) Arrhenius plots obtained based on the relaxation time τ at different temperatures. (e) Activation energy (Ea) of BED-xy samples. (f) Thermal expansion coefficient of BED-xy samples obtained by expansion coefficient test.

[0053] Fig.11 Shown are (a) photos of the BED-4-1 sample before and after healing and the healed film after twisting and stretching. (b) Stress-strain curves of the BED-4-1 and (c) BED-3-1.5 samples before and after healing. (d) Healing efficiency of the BED-xy sample healed at 170°C for 30 minutes.

[0054] Fig.12 Optical microscopy images of BED-4-1 and BED-3-1.5 samples before (a, c) and after (b, d) healing are shown.

[0055] Fig.13 Figure 2 shows (a) the recycling process of the BED-xy sample. (b) the stress-strain curves of the recycled BED-4-1 sample and the virgin BED-4-1 sample. (c) the stress-strain curves of the recycled sample and the virgin BED-3-1.5 sample. (d) and (e) the mechanical property recovery rates of the BED-xy sample recycled for 1 hour and 2 hours.

[0056] Fig.14 The stress-strain curves with the addition of different sulfur-containing modifiers are shown (a) lipoic acid (LA) (b) 4',4-dimercaptodiphenyl sulfide (TBBT) (c) dithiothreitol (DTT) (d) 4,4-diaminodiphenyl disulfide (APDS) (e) 2,5-diamino-1,4-benzenedithiol dihydrochloride (DPDD) (f) bis(4-aminophenyl) sulfide (TDA) (g) p-toluene disulfide (PTD).

[0057] Fig.15 The vulcanization curves of polyisoprene rubber with different vulcanization regulators added are shown: (a) 4-aminothiophenol (b) 4-aminothiophenol and 40 parts of carbon black (CB) (c) 3-aminothiophenol (d) 3-aminothiophenol and 40 parts of carbon black (e) 3-aminothiophenol (f) 2-aminothiophenol and 40 parts of carbon black.

[0058] Fig.16 The stress-strain curves of polyisoprene rubber with different vulcanization regulators added are shown: (a) 4-aminothiophenol (b) 4-aminothiophenol and 40 parts of carbon black (CB) (c) 3-aminothiophenol (d) 3-aminothiophenol and 40 parts of carbon black (e) 3-aminothiophenol (f) 2-aminothiophenol and 40 parts of carbon black.

[0059] Fig.17 Shows the vulcanization curves of SBR and BR with different amounts of vulcanization regulator added (a) SBR (b) BR.

[0060] Fig.18 Shown are the stress-strain curves of SBR and BR with different amounts of vulcanization regulator added (a) SBR (b) BR. DETAILED DESCRIPTION

[0061] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0062] The raw materials used in the embodiments of the present invention are:

[0063] The polyisoprene rubber (PIP in this specification) is IR70. The styrene-butadiene rubber is YH2605, and the butadiene rubber is homemade in the laboratory. Sulfur, vulcanization accelerator CBS (N-cyclohexyl-2-benzothiazole sulfonamide), antioxidant TMQ (poly (1,2-dihydro-2,2,4-trimethylquinoline)), antioxidant 4020 (N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine), zinc oxide (ZnO) and stearic acid (SA) were purchased from Adamas Chemical Company.

[0064] The following examples adopt a double-roll milling method to prepare samples, and the specific operation steps are as follows:

[0065] 1. Use appropriate roller distance to pass polyisoprene rubber 3-6 times;

[0066] 2. Add ZnO and SA and thin it for 3-6 times;

[0067] 3. Add TMQ and antioxidant 4020 and mix for 3-5 times, then add fillers such as benzenedithiol (BED) and butanedithiol (BTD) and mix for 3-6 times;

[0068] 4. Add sulfur and CBS and pass through 3-6 times;

[0069] 5. Scrape the double-roller medicine off and pass it 5-8 times with the minimum roller distance.

[0070] The vulcanization process used in the following examples is: using a flat plate vulcanizer, determining the hot pressing vulcanization time according to T90 at 143° C. and a pressure of 10 MPa, and high temperature vulcanization molding.

[0071] Example 1

[0072] A modified vulcanized rubber is prepared by a double-roll open mill, and the specific steps are as follows.

[0073] 1. Use appropriate roller distance to pass 100 parts by weight of polyisoprene rubber through 5 times.

[0074] 2. Add 5 parts by weight of ZnO and 2 parts by weight of SA and thin it 5 times.

[0075] 3. Add 1 part by weight of TMQ and antioxidant 4020 and mix for 3-5 times, then add 0.125 part by weight of benzenedithiol (BED) and mix for 5 times.

[0076] 4. Add 2 parts by weight of sulfur and 1 part by weight of CBS and pass through 5 times.

[0077] 5. Scrape the medicine off the double rollers and pass it 5 times with the minimum roller distance.

[0078] The obtained product was named BED-0.125.

[0079] Example 2

[0080] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that the amount of benzenedithiol (BED) added was 0.25 parts by weight. The obtained product was named BED-0.25.

[0081] Example 3

[0082] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that the amount of benzenedithiol (BED) added was 0.5 parts by weight. The obtained product was named BED-0.5.

[0083] Example 4

[0084] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that the amount of benzenedithiol (BED) added was 1 part by weight. The obtained product was named BED-1.

[0085] Example 5

[0086] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that the amount of benzenedithiol (BED) added was 2 parts by weight. The obtained product was named BED-0.2.

[0087] Example 6

[0088] A modified vulcanized rubber was prepared by a two-roll milling method in the same manner as described in Example 1, except that 0.125 parts by weight of butanedithiol (BTD) was used instead of benzenedithiol (BED) in step 3. The obtained product was named BTD-0.125.

[0089] Example 7

[0090] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 0.25 parts by weight of butanedithiol (BTD) was used instead of benzenedithiol (BED) in step 3. The obtained product was named BTD-0.25.

[0091] Example 8

[0092] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 0.5 parts by weight of butanedithiol (BTD) was used instead of benzenedithiol (BED) in step 3. The obtained product was named BTD-0.5.

[0093] Example 9

[0094] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 1 part by weight of butanedithiol (BTD) was used instead of benzenedithiol (BED) in step 3. The obtained product was named BTD-1.

[0095] Example 10

[0096] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 2 parts by weight of butanedithiol (BTD) was used instead of benzenedithiol (BED) in step 3. The obtained product was named BTD-2.

[0097] Embodiment 11

[0098] A modified vulcanized rubber is prepared by a double-roll open mill, and the specific steps are as follows.

[0099] 1. Use appropriate roller distance to pass 100 parts by weight of polyisoprene rubber through 5 times.

[0100] 2. Add 5 parts by weight of ZnO and 2 parts by weight of SA and thin it 5 times.

[0101] 3. Add 1 part by weight of TMQ and antioxidant 4020 and mix for 3-5 times, then add 3 parts by weight of benzenedithiol (BED) and mix for 5 times.

[0102] 4. Add 2 parts by weight of sulfur and 1 part by weight of CBS and pass through 5 times.

[0103] 5. Scrape the medicine off the double rollers and pass it 5 times with the minimum roller distance.

[0104] The obtained product was named BED-3-1.

[0105] Example 12

[0106] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 11, except that the amount of benzenedithiol (BED) added was 4 parts by weight. The obtained product was named BED-4-1.

[0107] Embodiment 13

[0108] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 11, except that the amount of benzenedithiol (BED) added was 5 parts by weight. The obtained product was named BED-5-1.

[0109] Embodiment 14

[0110] A modified vulcanized rubber was prepared by a two-roll mill, the preparation method of which was the same as that described in Example 11, except that the amount of CBS added was 1.5 parts by weight. The obtained product was named BED-3-1.5.

[0111] Embodiment 15

[0112] A modified vulcanized rubber was prepared by a two-roll mill, the preparation method of which was the same as that described in Example 12, except that the amount of CBS added was 1.5 parts by weight. The obtained product was named BED-4-1.5.

[0113] Example 16

[0114] A modified vulcanized rubber was prepared by a two-roll mill, the preparation method of which was the same as that described in Example 13, except that the amount of CBS added was 1.5 parts by weight. The obtained product was named BED-5-1.5.

[0115] Embodiment 17

[0116] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that lipoic acid (LA) was used instead of benzenedithiol in an amount of 0.5 parts by weight. The obtained product was named LA-0.5.

[0117] Embodiment 18

[0118] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that lipoic acid (LA) was used instead of benzenedithiol in an amount of 1 part by weight. The obtained product was named LA-1.

[0119] Embodiment 19

[0120] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 4',4-dimercaptodiphenyl sulfide (TBBT) was used instead of benzenedithiol in an amount of 0.5 parts by weight. The obtained product was named TBBT-0.5.

[0121] Embodiment 20

[0122] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 4',4-dimercaptodiphenyl sulfide (TBBT) was used instead of benzenedithiol in an amount of 1 part by weight. The obtained product was named TBBT-1.

[0123] Embodiment 21

[0124] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that dithiothreitol (DTT) was used instead of benzenedithiol in an amount of 1 part by weight. The obtained product was named DTT-1.

[0125] Embodiment 22

[0126] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 4,4-diaminodiphenyl disulfide (APDS) was used instead of benzenedithiol in an amount of 0.5 parts by weight. The obtained product was named APDS-0.5.

[0127] Embodiment 23

[0128] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 4,4-diaminodiphenyl disulfide (APDS) was used instead of benzenedithiol in an amount of 1 part by weight. The obtained product was named APDS-1.

[0129] Embodiment 24

[0130] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 2,5-diamino-1,4-benzenedithiol dihydrochloride (DPDD) was used instead of benzenedithiol in an amount of 0.5 parts by weight. The obtained product was named DPDD-0.5.

[0131] Embodiment 25

[0132] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 2,5-diamino-1,4-benzenedithiol dihydrochloride (DPDD) was used instead of benzenedithiol in an amount of 1 part by weight. The obtained product was named DPDD-1.

[0133] Embodiment 26

[0134] A modified vulcanized rubber was prepared by a two-roll milling method in the same manner as described in Example 1, except that bis(4-aminophenyl) sulfide (TDA) was used instead of benzenedithiol in an amount of 0.5 parts by weight. The obtained product was named TDA-0.5.

[0135] Embodiment 27

[0136] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that bis(4-aminophenyl) sulfide (TDA) was used instead of benzenedithiol in an amount of 1 part by weight. The obtained product was named TDA-1.

[0137] Embodiment 28

[0138] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that p-toluene disulfide (PTD) was used instead of benzenedithiol in an amount of 0.5 parts by weight. The obtained product was named PTD-0.5.

[0139] Embodiment 29

[0140] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that p-toluene disulfide (PTD) was used instead of benzenedithiol in an amount of 1 part by weight. The obtained product was named PTD-1.

[0141] Embodiment 30

[0142] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 4-aminobenzenethiol was used instead of benzenedithiol in an amount of 0.5 parts by weight. The obtained product was named PIP-d-ABTH-0.5phr.

[0143] Embodiment 31

[0144] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 4-aminothiophenol was used instead of benzenedithiol, and the addition amount was 1 part by weight. The obtained product was named PIP-d-ABTH-1phr.

[0145] Embodiment 32

[0146] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 4-aminobenzenethiol was used instead of benzenedithiol in an amount of 2 parts by weight. The obtained product was named PIP-d-ABTH-2phr.

[0147] Embodiment 33

[0148] A modified vulcanized rubber was prepared by a two-roll milling method, and the preparation method was the same as that described in Example 1, except that 4-aminothiophenol was used instead of benzenedithiol in an amount of 5 parts by weight. The obtained product was named PIP-d-ABTH-5phr.

[0149] Embodiment 34

[0150] A modified vulcanized rubber was prepared by a two-roll mill in the same manner as described in Example 30, except that 40 parts of carbon black (CB) were added. The resulting product was named PIP-d-ABTH-0.5phr-CB40.

[0151] Embodiment 35

[0152] A modified vulcanized rubber was prepared by a two-roll milling process in the same manner as described in Example 31, except that 40 parts of carbon black (CB) were additionally added. The resulting product was named PIP-d-ABTH-1phr-CB40.

[0153] Embodiment 36

[0154] A modified vulcanized rubber was prepared by a two-roll milling process in the same manner as described in Example 32, except that 40 parts of carbon black (CB) were additionally added. The resulting product was named PIP-d-ABTH-2phr-CB40.

[0155] Embodiment 37

[0156] A modified vulcanized rubber was prepared by a two-roll milling process in the same manner as described in Example 33, except that 40 parts of carbon black (CB) were added. The resulting product was named PIP-d-ABTH-5phr-CB40.

[0157] The operation of adding 3-aminothiophenol and 2-aminothiophenol is similar to that of Examples 30-37 and will not be described in detail.

[0158] Embodiment 38

[0159] A modified vulcanized rubber is prepared by a double-roll open mill, and the specific steps are as follows.

[0160] 1. Use appropriate roller distance to pass 100 parts by weight of styrene-butadiene rubber through the roller 5 times.

[0161] 2. Add 5 parts by weight of ZnO and 2 parts by weight of SA and thin it 5 times.

[0162] 3. Add 1 part by weight of TMQ and antioxidant 4020 and mix for 3-5 times, then add 0.5 part by weight of benzenedithiol (BED) and mix for 5 times.

[0163] 4. Add 2 parts by weight of sulfur and 1 part by weight of CBS and pass through 5 times.

[0164] 5. Scrape the medicine off the double rollers and pass it 5 times with the minimum roller distance.

[0165] The obtained product was named SBR-0.5phr.

[0166] The steps for preparing the modified vulcanized rubber containing other parts of benzenedithiol are similar to those in this embodiment and will not be described in detail.

[0167] Embodiment 39

[0168] A modified vulcanized rubber is prepared by a double-roll open mill, and the specific steps are as follows.

[0169] 1. Use appropriate roller distance to pass 100 parts by weight of butyl rubber through 5 times.

[0170] 2. Add 5 parts by weight of ZnO and 2 parts by weight of SA and thin it 5 times.

[0171] 3. Add 1 part by weight of TMQ and antioxidant 4020 and mix for 3-5 times, then add 0.5 part by weight of benzenedithiol (BED) and mix for 5 times.

[0172] 4. Add 2 parts by weight of sulfur and 1 part by weight of CBS and pass through 5 times.

[0173] 5. Scrape the medicine off the double rollers and pass it 5 times with the minimum roller distance.

[0174] The resulting product was named BR-0.5phr.

[0175] The operating steps for preparing modified vulcanized rubber containing other parts of benzenedithiol are the same as those in Example 39 and are not described in detail.

[0176] Test Case

[0177] Test Method

[0178] The vulcanization curve test was characterized by RPA8000 rubber processing analyzer; the tensile test was carried out by American INSTRON68TM-10, and the tensile rate was 100mm / min.

[0179] The DCS (Q200, TA) test is used to observe the exothermic phenomenon of chemical reactions during the sample heating process. The heating rate is 3°C / min, the crucible is made of aluminum, and the sample mass is 5-7mg.

[0180] Determination of the content of monosulfide bonds, disulfide bonds and polysulfide bonds in vulcanized rubber by chemical probe method:

[0181] 1. Place the sample in toluene to fully swell and then dry it, and measure the crosslink density (Xtotal).

[0182] 2. After the cross-link density (Xtotal) is determined, the sample is placed in toluene to fully swell, and then isopropyl mercaptan and piperidine are added and the swelling is continued for 4 hours to destroy the polysulfide bonds. The sample is then taken out and the cross-link density (X1) is determined using the equilibrium swelling method, and the polysulfide bond ratio is: (Xtotal-X1) / Xtotal.

[0183] 3. After the polysulfide bond ratio is determined, the sample is placed in a 1-hexanethiol pyridine solution for swelling for 48 hours to destroy the disulfide bonds. Then, the sample is taken out and the crosslinking density (X2) is determined using the equilibrium swelling method. The disulfide bond ratio is: (X1-X2) / Xtotal.

[0184] 4. After the disulfide bond ratio is determined, the sample is placed in a toluene solution of iodomethane to swell for 72 hours, and then heated and swelled for 96 hours to destroy the single sulfur bonds. Then, the sample is taken out and the crosslinking density (X2) is determined using the equilibrium swelling method. The single sulfur bond ratio is: (X2-X3) / Xtotal, and the carbon-carbon bond ratio is: X3 / Xtotal.

[0185] FT-IR spectra were measured on a Nicoleti S10 using ATR-IR mode. In dynamic FTIR, the sample was fixed to pre-stretch to a predetermined strain before measurement.

[0186] Dynamic mechanical analysis (DMA) was performed using a Q800 (TA Instruments); for temperature sweep mode, the sample was heated from -80°C to 150°C in tension mode at a rate of 5°C / min, a frequency of 1 Hz, and an amplitude of 15 μm. For stress relaxation, the strain was kept at 40%. Creep tests were performed at a constant stress of 0.2 MPa for 30 min followed by recovery for 30 min. The test temperatures for stress relaxation were 110°C, 120°C, 130°C, and 140°C, with a strain of 5%.

[0187] Synchrotron wide-angle X-ray diffraction (WAXD) was tested at the BL16B1 beamline of the Shanghai Synchrotron Radiation Source (SSRF). The wavelength of the X-ray was 0.124 nm, and the air background was subtracted during the sample processing. The rectangular sample was stretched using a homemade stretching machine at a stretching rate of 12.5 mm / min, and the signal was continuously collected in situ using a MARCCD detector with an exposure time of 5 s. The distance from the sample to the detector was calibrated using CeO2, and the result was 187.5 mm.

[0188] Test Results

[0189] 1. Figure 1 The characterization results of the BED-x samples prepared in Examples 1-5 and the BTD-x samples prepared in Examples 6-10 are shown.

[0190] Among them, the cross-linking dynamics of the rubber sample was determined by monitoring the change in curing torque at 143°C. The optimal curing time (T90) refers to the time required for the torque to reach 90% of the maximum value. The torque difference (ΔS) is the difference between the maximum torque (MH) and the minimum torque (ML), which indicates the overall cross-linking density of the vulcanized rubber. It can be found that the addition of a small amount of BED and BTD monomers can significantly increase the vulcanization rate, and the maximum torque can be observed within 10 minutes as the vulcanization proceeds. The reason is that the -SH group can promote the vulcanization process, thereby speeding up the vulcanization rate. In addition, the maximum torque value of the BED-x sample continues to increase with the increase of BED content, but too much monomer will reduce the torque ( Figure 1 ad). This is consistent with the results of the equilibrium expansion test ( Figure 1 e). For example, the torque and crosslink density of the BED-2 sample are the smallest. Interestingly, the maximum torque value of the BTD-x sample decreases with the increase of BTD content. The reason is that the -SH group of the BTD monomer is more active than the -SH group of the BED monomer. Excessive addition will hinder the crosslinking reaction and reduce the torque, which is also consistent with the results of the equilibrium expansion test ( Figure 1 f).

[0191] 2. Figure 2 The DSC curves of the BED-x samples prepared in Examples 1-5 and the BTD-x samples prepared in Examples 6-10 are shown.

[0192] From the DSC data, we found that there was only one Tg when a low fraction of filler was added, but when a high fraction of filler was added, two Tgs appeared, and the positions of the high Tgs were also very close. We speculate that this may be because when a high fraction of filler is added, a high concentration of free radicals will be formed in the filler aggregation area, causing cis-isoprene to be converted into trans-isoprene structure, resulting in the appearance of a new Tg peak at around 20 degrees.

[0193] 3. Figure 3 The Fourier transform infrared spectra and the contents of disulfide bonds and polysulfide bonds of the BED-x samples prepared in Examples 1-5 and the BTD-x samples prepared in Examples 6-10 are shown.

[0194] Fourier transform infrared spectroscopy was used to analyze the type of cross-linking bonds. Figure 3 a and 3b, 459cm -1 The absorption peaks at 619 cm-1 and 620 cm-2 correspond to the stretching vibrations of disulfide bonds (CSSC) and polysulfide bonds (C-SX-C), respectively, indicating the presence of disulfide bonds and polysulfide bonds in the cross-linked system. Interestingly, we did not observe the single sulfur bond (CS) at 619 cm-1. -1 and 1445cm -1 This indicates that there is no single sulfur bond in the cross-linked sample.

[0195] We used a chemical probe method to further analyze the composition of cross-links in the vulcanized network. The cross-linked rubber sample was placed in a solution of 2-propanethiol and piperidine to break the polysulfide bonds and determine the content of polysulfide bonds. The dried cross-linked rubber sample was placed in a 1-hexanethiol solution under argon to break the disulfide bonds and determine the content of disulfide bonds. However, all cross-linked samples treated with 1-hexanethiol dissolved, indicating that there were no monosulfide bonds. This is also consistent with the results of Fourier transform infrared spectroscopy. Figure 3 As shown in Figure c, the addition of 0.5 and 1 phr of BED monomer significantly increased the content of polysulfide bonds. However, excess BED monomer (BED-2) decreased the content of polysulfide bonds. Figure 3 As shown in Figure d, the addition of 0.125phr of highly active BTD monomer significantly increased the content of polysulfide bonds. At the same time, the addition of excess BTD monomer also reduced the content of polysulfide bonds. Interestingly, the addition of 2phr of BTD monomer (BTD-2) changed the cross-linking structure, and the cross-linking network was completely composed of polysulfide bonds. These results confirm the type and content of cross-links in the rubber samples.

[0196] 4. Figure 4 The mechanical properties test results of the BED-x samples prepared in Examples 1-5 and the BTD-x samples prepared in Examples 6-10 are shown.

[0197] Typical tensile curves of BED-x and BTD-x samples are shown in Figure 2. Figure 4 a and 4b. It is worth noting that increasing the BED monomer content leads to significant changes in mechanical properties. In general, increasing the BED monomer content can improve tensile strength, tear strength and toughness. Among them, the highest mechanical properties are obtained by adding 0.5phr (BED-0.5) and 1phr (BED-1) of BED monomer. However, excessive addition (BED-2) will hinder the crosslinking reaction and reduce the mechanical properties. In addition, the highest mechanical properties are obtained by adding 0.125phr (BTD-0.125) of BTD monomer. However, increasing the BTD monomer content also leads to a decrease in tensile strength, tear strength and toughness. From the crosslinking density and torque results ( Figure 1 ) It can be seen that the addition of excessive monomers will hinder the cross-linking reaction and lead to reduced mechanical properties. Figure 4 As shown in c and 4d, we selected three samples with the best mechanical properties as representative samples to study the strengthening mechanism. Among them, the tensile strength, tear strength and toughness of BED-1 (30.4MPa, 31.3kN / m and 73.1MJ / m3, respectively) are significantly higher than those of PIP (22.1MPa, 25.7kN / m and 47.1MJ / m3, respectively).

[0198] like Figure 4To further understand the mechanism of mechanical property enhancement, we used the Mooney-Rivlin equation to estimate the entanglement network. It is generally believed that Gc is related to the permanent cross-linked network, while Ge is related to the transient entanglement. Figure 4 f shows the fitted values ​​of Gc and Ge. It can be seen that the permanent modulus Gc and entanglement modulus Ge of the representative samples are higher than those of PIP. It is worth noting that the entanglement modulus Ge values ​​of BED-0.5 and BED-1 are more than twice that of PIP, which greatly promotes the improvement of mechanical properties. The Gc and Ge values ​​of BTD-0.125 are higher than those of PIP, but lower than those of BED-0.5 and BED-1, so the mechanical properties are higher than those of PIP, but not as good as those of BED-0.5.

[0199] 5. Figure 5 The performance measurement results of BED-0.5, BED-1 and BTD-0.125 samples are shown.

[0200] Through synchrotron radiation data, it can be found that compared with PIP, BED-0.5 and BED-1 have the smallest initial strain of SIC and the highest crystallinity. Studies have shown that the initial strain of SIC has nothing to do with the cross-linking density of the cross-linked network, but is related to entanglement and short chains. From the Mooney-Rivlin results ( Figure 4 f) It can be seen that the entanglement modulus (Ge) of BED-0.5 and BED-1 samples is the highest, so the initial strain of SIC is the smallest. At the same time, the chemical probe test ( Figure 3 c), we analyzed that the addition of BED monomer significantly increased the content of polysulfide bonds, and the increase in polysulfide bonds led to better molecular chain flexibility and enhanced SIC ability, so BED-0.5 and BED-1 samples had higher crystallinity. In addition, the entanglement modulus (Ge) of the BTD-0.125 sample was only slightly higher than that of PIP, so the SIC starting strains of the two samples were similar. However, the polysulfide content of BTD-0.125 (polysulfide bonds, 84.1%) was much higher than that of PIP (polysulfide bonds, 74.6%). Therefore, BTD-0.125 has higher crystallinity and thus higher mechanical properties. However, the addition of excessive monomers will hinder the cross-linking reaction, reduce the content of polysulfide bonds, and lead to a significant decrease in crystallinity. The excellent mechanical properties of BED-0.5 and BED-1 are precisely due to this excellent SIC ability.

[0201] 6. Figure 6 The creep resistance test results of BED-0.5, BED-1 and BTD-0.125 samples are shown.

[0202] like Figure 6As shown in b-6f, the representative samples show similar creep trends as the temperature increases, and the dimensional stability begins to decrease rapidly after 120°C. This is because the crosslinking bonds in the vulcanized network begin to exchange rapidly at this temperature. The BED-0.5 sample has excellent creep resistance, and its creep strain and residual strain are the smallest at all test temperatures compared to other rubber samples. This may be due to the highest entanglement modulus ( Figure 4 f). Topological entanglement severely restricts chain motion in the polymer network and acts as an anchor, thereby optimizing dimensional stability. In contrast, the BTD-0.125 sample has the worst creep performance at all temperatures. This may be due to the highest content of polysulfide bonds ( Figure 3 d). The activation energy of polysulfide bonds is low, resulting in a fast bond exchange rate, which is fatal to creep performance. At the same time, the entanglement modulus is also much lower than that of the BED-0.5 sample. In general, the creep performance of the BTD-0.125 sample is the worst.

[0203] Based on the above analysis, we proposed a simple method to prepare high-performance polyisoprene rubber by adjusting the composition and content of disulfide bonds and polysulfide bonds and increasing the entanglement degree in the vulcanization network. Adding an appropriate amount of BED monomer can increase the polysulfide bond content and entanglement degree in the system, thereby improving the SIC capacity and significantly improving the mechanical properties. At the same time, the high entanglement modulus also gives the sample excellent dimensional stability.

[0204] To further explore the potential of BED monomer, we also prepared samples with high content of BED monomer (ie, Examples 11-16), which will be discussed in the following.

[0205] 7. Figure 7 The characterization results of the BED-xy samples prepared in Examples 11-16 are shown.

[0206] like Figure 7 As shown in Figs. 7a and 7b, at the same S / A ratio, the vulcanization rate and maximum torque decrease significantly with the increase of BED monomer content. At the same time, at the same BED monomer content, the addition of additional accelerator can significantly increase the vulcanization rate and torque. This is because excessive addition of monomers will hinder the crosslinking reaction and reduce the torque. This is consistent with the results of the equilibrium expansion test ( Figure 7 c and 7d). As the BED monomer content increases, the cross-linking density of the samples gradually decreases.

[0207] 8. Figure 8 The Fourier transform infrared spectra, disulfide bond and polysulfide bond contents and recovery performance tests of the BED-xy samples prepared in Examples 11-16 are shown.

[0208] Fourier transform infrared spectroscopy was used to analyze the type of cross-linking bonds. Figure 8As shown in a, 451cm -1 The absorption peaks at 619cm correspond to disulfide bonds and polysulfide bonds. -1 and 1445cm -1 The absorption peak at corresponds to the single sulfur bond. Interestingly, we did not observe the absorption peak of the single sulfur bond in BED-4-1 and BED-5-1 samples. However, the absorption peaks of the three cross-linking bonds can be clearly observed in other samples. We also used the chemical probe method to further analyze the composition of the cross-linking bonds in the sulfurized network. Figure 8 As shown in b, the vulcanization network of BED-4-1 and BED-5-1 samples is composed entirely of polysulfide bonds and does not contain any disulfide bonds and monosulfide bonds. In other rubber samples, the vulcanization network is composed of three types of cross-linked bonds. However, the number of each type of cross-linked bonds varies. This is also consistent with the results of Fourier transform infrared spectroscopy. These results confirm the type and content of cross-linked bonds in the cross-linked rubber samples. In addition, we also compared the Fourier transform infrared spectra of BED-4-1 and BED-5-1 samples before and after recovery. As Figure 8 As shown in Figs. c and 8d, after recycling at 170 °C for 2 hours, we can observe an obvious single sulfur bond peak. Combined with the results of the chemical probe test, this is because disulfide bonds and polysulfide bonds are constantly exchanged during the recycling process, thereby converting into single sulfur bonds, resulting in a decrease in the content of disulfide bonds and polysulfide bonds in the sulfurized network and an increase in the content of single sulfur bonds. The BED-4-1 and BED-5-1 samples are completely composed of polysulfide bonds in the sulfurized network, so they have excellent recyclability and self-healing properties.

[0209] 9. Fig. 9 The mechanical properties and creep resistance test results of the BED-xy samples prepared in Examples 11-16 are shown.

[0210] Typical stress-strain curves of BED-xy are shown in Fig. 9 a. As the BED monomer content increases, the tensile strength of the sample decreases slightly. At the same time, the addition of additional accelerators can significantly increase the tensile strength. Combining the results of the vulcanization curve and the equilibrium expansion experiment ( Figure 7 ), excessive addition of BED monomer will hinder the cross-linking reaction and reduce the torque, resulting in a slight decrease in tensile strength. Although the addition of BED monomer will slightly reduce the tensile strength, the addition of an appropriate amount of BED monomer will change the composition of the cross-linking bonds in the vulcanization network, making the cross-linked rubber sample have excellent recyclability and self-healing properties.

[0211] Dimensional stability is also a crucial property for recyclability and self-healing rubber elastomers. Fig. 9As shown in Figures 9c and 9d, increasing the content of BED monomer will reduce the creep performance, because the addition of BED monomer will increase the content of polysulfide bonds in the vulcanization network, and polysulfide bonds have rapid bond exchange ability, so it will reduce the creep performance. At the same time, increasing the content of BED monomer will reduce the crosslinking density, resulting in a decrease in creep performance. In addition, increasing the accelerator content will reduce the polysulfide bond content, increase the single sulfur bond content and crosslinking density, and thus improve the creep performance. Although the addition of BED monomer will reduce the creep performance, the integrity of the material can still be maintained at 90°C without breaking. This is crucial for the practical use of rubber products.

[0212] 10. Fig.10 Further test results of the properties of the BED-xy samples prepared in Examples 11-16 are shown.

[0213] Stress relaxation is an important characteristic of dynamic covalent polymer network (DCPN) polymers. In order to study the stress relaxation rate and activation energy, we conducted stress relaxation experiments. Fig.10 As shown in Figure 2, the stress of all samples can relax to 1 / e of the initial stress within a certain period of time. Fig.10 As shown in Figures ac, the three samples can significantly release stress over time, indicating that the network can flow at the evaluation temperature. In addition, the relaxation rates of BED-4-1 and BED-5-1 samples are faster and the characteristic relaxation time is shorter. To further analyze the stress relaxation behavior, Fig.10 The activation energy (Ea) was obtained from the slope of the fitted line in d. Fig.10 e summarizes the corresponding fitting parameters. The activation energy (Ea) of BED-4-1 (62.91 kJ / mol) and BED-5-1 (64.18 kJ / mol) is significantly lower than that of BED-3-1.5 (72.55 kJ / mol). This result indicates that BED-4-1 and BED-5-1 samples have advantages in the post-treatment process. The bond energy of a single sulfur bond is the highest, followed by a disulfide bond, while the bond energy of a polysulfide bond is the lowest. Combined with the results of the chemical probe test, the BED-4-1 sample has the lowest activation energy because it only contains polysulfide bonds, while the BED-3-1.5 sample contains the most single sulfur bonds and therefore has the highest activation energy. In addition, the topological transition temperature (Tv) was measured by a dilution test. As Fig.10 As shown in Figure f, with the increase of promoter content, the cross-linking density and the content of single sulfur bonds increase, which leads to a rapid increase in Tv. At the same time, with the increase of BED monomers, the cross-linking density decreases and the content of polysulfide bonds increases, resulting in a decrease in Tv. When Tv is exceeded, the exchange reaction is strongly accelerated and the topological structure is rearranged. This phenomenon is also more conducive to subsequent recycling and self-healing experiments.

[0214] 11. Fig.11 and 12The self-healing performance test results of the BED-xy samples prepared in Examples 11-16 are shown.

[0215] The self-healing ability was tested by cutting the rubber film into two pieces with a blade and then putting them together to heal at 170°C for about 30 minutes. For better observation, one of the samples was painted black. Fig.11 As shown in a, the BED-4-1 sample can withstand large strains due to the remodeling of the polysulfide bonds at the fracture interface. The self-healing efficiency is quantified by tensile tests. Fig.11 b and Fig.11 c shows representative stress–strain curves of BED-4-1 and BED-3-1.5 samples after healing at 170 °C for 30 min. Fig.11 d summarizes the healing efficiency parameters. Obviously, the healing efficiency of BED-4-1 tensile strength (89.8%) is significantly higher than that of BED-3-1.5 (15.4%). The reason is that the high cross-linking density not only restricts the movement of the chains, but also hinders the dynamic exchange of disulfide bonds and polysulfide bonds to a certain extent. The BED-3-1.5 sample has the highest cross-linking density and the highest content of single sulfur bonds in the vulcanization network. Therefore, the BED-3-1.5 sample has the lowest healing efficiency. In addition, the BED-4-1 and BED-5-1 samples have appropriate cross-linking densities and the vulcanization networks are completely composed of polysulfide bonds, so they have excellent self-healing properties.

[0216] In addition, a small scratch was made on the surface of the cross-linked rubber sample with a blade, and then the scratched rubber sample was placed in a vacuum oven at 170°C for about 30 minutes. The healing process before and after the scratch was healed was observed using an optical microscope. The optical microscope image is shown in Figure 2. Fig.12 As shown. After repairing the BED-4-1 sample at 170°C for about 30 minutes, the scratches on the surface have healed, leaving only faint traces. However, the scratches on the BED-3-1.5 sample are clearly visible. Due to the presence of polysulfide bonds, the BED-4-1 sample has excellent self-healing ability. The poor self-healing ability of BED-3-1.5 is due to the high content of single sulfur bonds in the sulfide network. These results are consistent with previous research results.

[0217] 12. Fig.13 The recovery performance test results of the BED-xy samples prepared in Examples 11-16 are shown.

[0218] Once thermosetting materials are completely cured, they cannot be recycled. This will cause resource waste and environmental pollution. The disulfide bonds and polysulfide bonds in the vulcanized network of rubber samples will undergo exchange reactions under temperature stimulation. Cracks can be re-formed during the dynamic rearrangement of the network, so the cracked samples can restore their original properties, providing the possibility for the recycling and reprocessing of cross-linked rubber. Fig.13As shown in Fig. a, the cross-linked rubber sample was cut into pieces and hot-pressed at 170 °C for 1 h or 2 h to form new coherent samples, which proved the recyclability of the BED-xy sample. The stress-strain curves of BED-4-1 and the recycled samples are shown in Fig. Fig.13 b. Fig.13 d and 13e summarize the recovery parameters. Fig.13 As shown in Figure b, we found that the tensile strength of the BED-4-1 sample after 1 hour of recycling was the same as that of the original sample, which proved that the BED-4-1 sample had excellent recyclability. However, the elongation at break after recycling was significantly reduced. We speculate that the polysulfide bonds in the vulcanization network are continuously converted into single sulfur bonds through bond exchange, which reduces the flexibility of the molecular chain and increases the cross-linking density during the cycle, resulting in an increase in modulus and a decrease in elongation at break. In addition, we also found that the elongation at break increased after 2 hours of recycling. This is because the rubber sample aged in a continuous high temperature environment, resulting in a decrease in the cross-linking density, thereby increasing the elongation at break. This is also consistent with the results of the equilibrium swelling test. As Fig.13 As shown in Figure c, the recyclability of the BED-3-1.5 sample is very poor. This is due to the presence of single sulfur bonds in the sulfidation network, which cannot achieve effective bond exchange during the recycling process. In short, during the recycling process, disulfide bonds and polysulfide bonds are constantly exchanged and converted into single sulfur bonds, so the recyclability of the BED-4-1 sample is excellent.

[0219] 13. Fig.14 The mechanical properties test results of the rubber samples prepared in Examples 17-29 are shown.

[0220] It can be seen that adding different types of vulcanization regulators with similar BED structures can also significantly enhance the properties of rubber. This is of great significance for achieving the enhancement of isoprene rubber through simple processing methods.

[0221] 14. Fig.15 The vulcanization curves of the samples after adding different vulcanization regulators are shown.

[0222] It can be seen from the data that the addition of vulcanization regulator can significantly increase the vulcanization rate.

[0223] 15. Fig.16 Shows the mechanical properties test results of samples after adding different vulcanization regulators

[0224] It can be seen that the addition of different types of vulcanization regulators with BED-like structures can also significantly enhance the properties of rubber.

[0225] 16. Fig.17 The vulcanization curve results of styrene-butadiene rubber and butadiene rubber after adding vulcanization regulators are shown.

[0226] The data show that in different types of rubber, vulcanization regulators can significantly increase the vulcanization rate.

[0227] 17. Fig.18 Shows the mechanical properties test results of styrene-butadiene rubber and butadiene rubber after adding vulcanization regulator.

[0228] It can be seen that the addition of different types of vulcanization regulators with similar BED structures can not only strengthen polyisoprene rubber but also significantly enhance the properties of other types of rubber.

[0229] Summarize

[0230] In the present invention, we report a facile strategy to prepare high-performance polyisoprene rubber by adjusting the composition and content of cross-links in the vulcanization network. In addition, we successfully prepared self-healing and recyclable polyisoprene rubber by further adjusting the cross-links in the vulcanization network so that they are completely composed of polysulfide bonds. We studied the composition and content of cross-links in polyisoprene rubber by Fourier transform infrared testing and chemical probe method. The tensile strength of BED-0.5 (30.22MPa) and BED-1 (30.42MPa) far exceeds that of PIP (22.03MPa) and is comparable to that of Malaysian NR. WAXD results show that the high content of polysulfide bonds in the vulcanization network increases entanglement and improves SIC ability, thereby significantly improving mechanical properties. At the same time, the high degree of entanglement also gives the rubber sample excellent dimensional stability. In addition, the introduction of the entire polysulfide bond in the sulfurized network can achieve topological rearrangement through the dynamic polysulfide bond rapid exchange reaction at high temperature, thus endowing BED-4-1 and BED-5-1 samples with self-healing ability and excellent recyclability. The maximum self-healing efficiency of the representative sample is 89.8%, and the tensile strength is as high as 5.6MPa.

[0231] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.

Claims

1. A method for preparing a vulcanized rubber having a vulcanization network structure regulated by a sulfur-containing regulator, characterized in that: The method comprises vulcanizing 100 parts by weight of raw rubber in the presence of 0.5-2 parts by weight of a sulfur-containing regulator, thereby obtaining vulcanized rubber with high mechanical properties and creep resistance.

2. The method according to claim 1, characterized in that The raw rubber is at least one of EPDM rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, polybutadiene rubber, butyl rubber, nitrile rubber, styrene / butadiene block copolymer, polyisoprene rubber, polynorbornene, unsaturated polyester rubber, epoxidized butadiene rubber, epoxidized isoprene rubber, epoxidized styrene / butadiene block copolymer and epoxidized styrene / isoprene block copolymer. The sulfur-containing regulator is a dithiol compound.

3. The method according to claim 2, characterized in that The sulfur-containing regulator is selected from at least one of the following compounds: Further, the sulfur-containing regulator is at least one of benzenedithiol (BED), lipoic acid (LA), 4',4-dithiodiphenyl sulfide (TBBT), dithiothreitol (DTT), 4,4-diaminodiphenyl disulfide (APDS), 2,5-diamino-1,4-benzenedithiol dihydrochloride (DPDD), bis(4-aminophenyl) sulfide (TDA), p-toluene disulfide (PTD), 4-aminothiophenol, 3-aminothiophenol, 2-aminothiophenol, 4-(phenylthio)aniline, butanedithiol and hexanedithiol. Furthermore, the weight proportion of the sulfur-containing regulator is preferably 0.5-1 part. Furthermore, the method further comprises adding 30-50 parts by weight of carbon black or white carbon black.

4. The method according to claim 1, characterized in that: The vulcanization includes adding a vulcanizing agent by double-roll milling or solution blending, and then vulcanizing and molding at a high temperature. Furthermore, the vulcanizing agent is sulfur, tetramethylthiuram disulfide (TMTD), dipentamethylenethiuram tetrasulfide (DPTT) (TRA), 4-(2-benzothiazolyl disulfide)morpholine (MDB), tetraethylthiuram disulfide (TETD), tetrabutylthiuram disulfide (TBTD), tetramethylthiuram tetrasulfide (TMTT), 4,4'-dimorpholine disulfide (DTDM), N,N-polysulfide bis(dimethylamine), N,N'-polysulfide bis(diethylamine), cyclohexylthiuram disulfide (CTS ... at least one of imine, dicumyl peroxide (DCP), di-tert-butyl peroxide (DTBP), 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DBPMH), benzoyl peroxide (BPO), 2,4-dichlorobenzoyl peroxide (DCPB), tert-butyl perbenzoate (TBPB), di-tert-butyl peroxyisopropylbenzene (BIPB), 3,3,5,7,7-pentamethyl-1,2,4-triepoxyhexane (PMTO), and cumyl hydroperoxide (CHP), Furthermore, the vulcanization further comprises adding an auxiliary agent, wherein the auxiliary agent comprises zinc oxide, stearic acid, an antioxidant, an anti-aging agent and / or a vulcanization accelerator. Furthermore, the antioxidant may be N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine, Furthermore, the antioxidant may be poly(1,2-dihydro-2,2,4-trimethylquinoline), Furthermore, the vulcanization accelerator may be N-cyclohexyl-2-benzothiazole sulfonamide, Furthermore, the weight proportion of the added vulcanizing agent is 1-3 parts, Furthermore, the weight proportions of zinc oxide, stearic acid, antioxidant, anti-aging agent and vulcanization accelerator added are 3-8 parts, 1-4 parts, 1-3 parts, 1-3 parts and 0.5-3 parts respectively.

5. A vulcanized rubber having a vulcanization network structure regulated by a sulfur-containing regulator, characterized in that: Prepared by the method according to any one of claims 1 to 4.

6. A method for preparing a vulcanized rubber having a vulcanization network structure regulated by a sulfur-containing regulator, characterized in that: The method comprises vulcanizing 100 parts by weight of raw rubber in the presence of 3-8 parts by weight of a sulfur-containing regulator, thereby obtaining vulcanized rubber with high mechanical properties and recycling and self-healing properties.

7. The method according to claim 6, characterized in that The raw rubber is at least one of EPDM rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, polybutadiene rubber, butyl rubber, nitrile rubber, styrene / butadiene block copolymer, polyisoprene rubber, polynorbornene, unsaturated polyester rubber, epoxidized butadiene rubber, epoxidized isoprene rubber, epoxidized styrene / butadiene block copolymer and epoxidized styrene / isoprene block copolymer. The sulfur-containing regulator is a dithiol compound.

8. The method according to claim 7, characterized in that The sulfur-containing regulator is selected from at least one of the following compounds: Further, the sulfur-containing regulator is at least one of benzenedithiol (BED), lipoic acid (LA), 4',4-dithiodiphenyl sulfide (TBBT), dithiothreitol (DTT), 4,4-diaminodiphenyl disulfide (APDS), 2,5-diamino-1,4-benzenedithiol dihydrochloride (DPDD), bis(4-aminophenyl) sulfide (TDA), p-toluene disulfide (PTD), 4-aminothiophenol, 3-aminothiophenol, 2-aminothiophenol, 4-(phenylthio)aniline, butanedithiol and hexanedithiol. Furthermore, the method further comprises adding 30-50 parts by weight of carbon black or white carbon black.

9. The method according to claim 6, characterized in that The vulcanization includes adding a vulcanizing agent by double-roll milling or solution blending, and then vulcanizing and molding at a high temperature. The vulcanizing agent is sulfur, tetramethylthiuram disulfide (TMTD), dipentamethylenethiuram tetrasulfide (DPTT) (TRA), 4-(2-benzothiazolyl disulfide)morpholine (MDB), tetraethylthiuram disulfide (TETD), tetrabutylthiuram disulfide (TBTD), tetramethylthiuram tetrasulfide (TMTT), 4,4'-dimorpholine disulfide (DTDM), N,N-polysulfobis(dimethylamine), N,N'-polysulfobis(diethylamine), cycloheptathiocyanate At least one of amine, diisopropylbenzene peroxide (DCP), di-tert-butyl peroxide (DTBP), 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DBPMH), benzoyl peroxide (BPO), 2,4-dichlorobenzoyl peroxide (DCPB), tert-butyl perbenzoate (TBPB), di-tert-butylperoxyisopropylbenzene (BIPB), 3,3,5,7,7-pentamethyl-1,2,4-triepoxyhexane (PMTO), and cumyl hydroperoxide (CHP), Furthermore, the vulcanization further comprises adding an auxiliary agent, wherein the auxiliary agent comprises zinc oxide, stearic acid, an antioxidant, an anti-aging agent and / or a vulcanization accelerator. Furthermore, the antioxidant may be N-1,3-dimethylbutyl-N'-phenyl-p-phenylenediamine, Furthermore, the antioxidant may be poly(1,2-dihydro-2,2,4-trimethylquinoline), Furthermore, the vulcanization accelerator may be N-cyclohexyl-2-benzothiazole sulfonamide, Furthermore, the weight proportion of the added vulcanizing agent is 1-3 parts, Furthermore, the weight proportions of zinc oxide, stearic acid, antioxidant, anti-aging agent and vulcanization accelerator added are 3-8 parts, 1-4 parts, 1-3 parts, 1-3 parts and 0.5-3 parts respectively. Preferably, the added vulcanization accelerator is in an amount of 1 part by weight.

10. A vulcanized rubber having a vulcanization network structure regulated by a sulfur-containing regulator, characterized in that: Prepared by the method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Double-crosslinking self-repairing epoxidized natural rubber and preparation method and application thereof

    CN109134986A

  • Butadiene styrene rubber with self-repairing function and preparation method

    CN110862589A

  • UV (ultraviolet) light-cured high polymer material capable of being repeatedly molded

    CN117209636A

  • Rubber composition

    JP1998025380A

  • Manufacturing method for rubber composition

    JP2010018705A

Cited By

  • Corrosion-resistant crane cable composite material and preparation method thereof

    CN120059329A